Guilt and the emotional underpinnings of human pro-sociality - Stanulewicz, Natalia Katarzyna (2018)
Pro-social acts are at the core of human relationships and proper functioning of society. Still, human pro-sociality is seen as unique, reaching beyond the kinship-based helping that is found in other species, such as primates. This uniqueness of human pro-sociality is recognised as closely related to another phenomenon specific to humans, and crucial for the maintenance of social relationships; namely, the presence of moral emotions. This thesis investigated emotional underpinnings of human pro-sociality after moral or social transgressions. The particular focus was placed on guilt – the emotion seen as most prototypical morally, and anger, its’ often under-studied relative. These two emotions have a unique standing in the context of the pro-sociality following from transgressions. They are associated with the perception of harm, injustice and norm violation that are core to transgression situations, and an action tendency to improve such situation, which behaving in a pro-social manner can be seen as. Nevertheless, only a few studies have examined guilt and anger jointly, in the context of pro-sociality, which stresses the need for an investigation of their relative influences. This thesis aimed to fill this gap in the literature. Chapter 1 introduces the topic of emotions and its role for pro-sociality, starting with the initial concept of emotions as the continuum of positive and negative affect, followed by more recent conceptualisation of emotions, in terms of their specificity and uniqueness. A particular emphasis is placed on the place of guilt and anger in the family of moral emotions, and their specific characteristics. Moreover, the role of pro-sociality as a mood-enhancing method is discussed, which might be used to suggest that guilt-based pro-sociality might not be so strongly relationship-focused, as presented in the literature. Chapter 2 presents a meta-analytical investigation of guilt and its role for pro-sociality. In this section, 112 studies were combined, providing an estimation of the medium effect size for the relationship between guilt and pro-sociality. Potential moderators were investigated as well, with a majority of them demonstrating no significant effects. Interestingly though, religiosity was found as a significant moderator of the guilt-pro-sociality relationship, with less religious countries showing a stronger effect size. The potential factors explaining this finding were presented. The link between guilt and self-punishment was also considered, providing more evidence that actions following from guilt might be seen as a mood enhancing strategy (at least when there is no option for repayment of one’s wrongdoing). Chapter 3 describes an experimental study investigating the association between moral transgression and subsequent pro-sociality. The charity dictator game was used as the opportunity for moral transgression. It was shown that moral transgression could lead to both increased and decreased pro-sociality, depending on the underlying emotional mechanism. Specifically, moral transgression via guilt led to increased pro-sociality, whereas via anger, to decreased pro-sociality. Some contextual factors (e.g., eyes prime, earning for oneself versus a charity) that could moderate which effect would prevail were examined. This result explains inconsistent findings reported previously in the literature. Additionally, it was shown that guilt does not always directly affect pro-sociality, as it might be followed by anger, and this sequential mechanism might negatively affect subsequent pro-sociality. Lastly, it was demonstrated that the effect of guilt and anger, following from a transgression, did not expand beyond the first pro-social opportunity, in line with the notion of pro-sociality as a mood-enhancing method. Chapter 4 introduces an experimental study aimed at the further exploration of the mechanism between guilt, anger, and subsequent pro-sociality. A context of failing one’s partner in a computer game was used to trigger moral emotions. The role of self-blame was also explored. Self-blame was predicted to act as the mechanism linking guilt with increased pro-sociality, whereas anger (a proxy of other-blame) was found to be the mechanism linking guilt with decreased pro-sociality. Some contextual factors, related to the perception of fairness, which could moderate which effect would prevail, were examined. Lastly, it was demonstrated that the effect of guilt did not expand beyond the first pro-social opportunity, in line with the notion of pro-sociality as a mood-enhancing method. Chapter 5 builds on the results in the previous section, by introducing manipulative intent as a factor determining the mechanism underlying the association between guilt, anger, and subsequent pro-sociality. A context of blood donation appeal was used to trigger moral emotions, making this study more applicable to the outside world. Contrary to the predictions, low rather than high manipulative intent in the appeal was shown to be the context where guilt led to decreased pro-sociality, via anger. The relationship between guilt and increased pro-sociality via responsibility (a proxy of self-blame) was significant under both levels of the manipulative intent present. Factors potentially explaining these findings are presented. This study provides evidence that the links between guilt and responsibility (self-blame) are not readily affected, whereas the connection between guilt and anger depends on situational context. Chapter 6 presents findings of the investigation into the lab-field correspondence in the pro-sociality domain, together with an examination of the possibility of a significant association of trait guilt and cost/risk perception of pro-social behaviours. Following from Piliavin’s cost-reward model, it was predicted that higher propensity of guilt-prone individuals to help might be based on their lowered appraisal of cost-risk of pro-social behaviours. Trait guilt was not related to cost-risk appraisals of pro-social behaviours though, suggesting that other mechanisms might be underlying the relationship between trait guilt and pro-sociality. Secondly, the issue of generalising findings from lab studies to real-life instances of pro-sociality was explored. The results have shown that pro-social behaviours used in labs were not equivalent (i.e., less costly and risky) to those in the real world. Pro-sociality appeared to be a non-unidimensional construct, which should be taken into account when investigating it in the future. Chapter 7 provides a general discussion of the results presented in this thesis, with the emphasis on their role in the field of emotions and human pro-sociality. Some implications of the present findings for charitable organisations and some avenues for future studies were presented as well. The findings presented in this thesis provide novel and exciting insight into the field of emotions and pro-sociality, in the context of transgression. The results suggest that even though guilt is widely studied in the context of pro-sociality, and has a robust effect on pro-sociality, anger should not be treated with less interest and attention in this regard. It was also shown that these two emotions are highly interrelated, co-occur in the context of transgression, and both have the potential to affect pro-sociality subsequent to transgression. The contextual factors, such as manipulative intent, appear to have a particular role in determining whether decreased or increased pro-sociality would occur after a violation, and which emotional mechanism would unfold. Therefore, neglecting one of these emotions in studies undermines the possibility of better understanding the emotional underpinnings of human pro-sociality. Thus, more research is warranted in the future. The similar research effort is needed for better understanding of the construct of pro-sociality itself, as human pro-sociality takes many forms which, as was shown, do not create a unidimensional construct. Thus, generalising findings from single instances of pro-social behaviour to general pro-sociality seems biased (especially to the high-cost behaviours), and this issue should be tackled in future research.